The Indo-West Pacific alpheid shrimp Athanas dimorphus Ortmann, 1894: first record for Brazil and the western Atlantic - Pachelle,Paulo P. G. (2011)
The alpheid shrimp Athanas dimorphus Ortmann, 1894, common and widespread throughout the Indo-West Pacific, is reported for the first time from Brazil, representing the first invasive alpheid species in Brazil, and the first species of the genus Athanas Leach, 1816 introduced to the western Atlantic. The present record is based on several specimens collected at two localities in Ceará, Pedra Rachada beach near the town of Paracuru, and Meireles beach in Fortaleza. Athanas dimorphus is very common at the second site, suggesting that a population of this species is now established in northwestern Brazil. An updated list of marine and freshwater decapods accidentally or voluntarily introduced to Brazil is provided.